Contribution of Internationalisation to SME Growth: Evidence from the Kenyan Manufacturing Sector - Safari, Kulondwa (Economics and Business, 2020)
Sub-Saharan African countries are among the poorest countries in the world and there is a need to develop their economies. Researchers suggest the promotion of small and medium-sized enterprises (SMEs) to foster economic development in countries. Internationalisation has been proved to be a key strategy for SME growth. This study investigates the effect of internationalisation on manufacturing SME growth in Kenya. Kenya is a developing country and the leading economy in the East African community. Using data from the World Bank enterprise survey, a sample of 94 SMEs operating in Kenya between 2013 and 2018 was selected. Multiple linear regression analysis using ordinary least square (OLS) was applied and the results revealed that internationalisation through direct exports contributed positively to the growth of manufacturing SMEs in Kenya. The findings of the study suggest that policy makers should promote internationalisation of SMEs in Kenya to improve the doing business environment in general and remove external barriers to internationalisation of SMEs at the national and international level in particular.